(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to know the role of strategic intelligence in achieving entrepreneurial sustainability in Baghdad Soft Drinks Company, with a purposive sample size (53), according to the comprehensive inventory. Therefore, the descriptive analytical approach was chosen for the purpose of collecting information. The program (SPSS V.24) was used to extract the results and test the main hypotheses of the research, which include the degree of association and influence of strategic intelligence in achieving entrepreneurial sustainability for the company under study. The research reached a number of results, the most important of which was that the company has a vision for the future through cooperation with employees and creating the required processes to involve everyone in implementing strategic visions. The company’s efforts indicate the presence of effective participation of employees in decision-making, as well as the company’s pursuit of building a future vision for the purpose of building a market share for the company. It became clear to the researcher through the practical aspect that there is an impact of the sub-dimensions of strategic intelligence on entrepreneurial sustainability.